1970
DOI: 10.1084/jem.132.6.1207
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Human Monocytes and Red Cells

Abstract: Red cells coated with IgG globulin are bound circumferentially about a central mononuclear cell or monocyte into a "rosette" (1). Attached red cells appear deformed and closely resemble the abnormal red cell morphology frequently observed in the peripheral blood of patients with Coombs positive hemolytic anemia associated with IgG antibodies. Although in some studies the monocyte receptor was specific for IgG globulin without specificity for the third component of complement (C3) (1, 2), in others a receptor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(51 citation statements)
references
References 18 publications
2
49
0
Order By: Relevance
“…The latter receptor is recognized by the formation of rosettes with sheep red blood cells coated with antibody and complement (EAC). Monocytes, histiocytes, and macrophages also have C3 receptors (7) but differ from B lymphocytes in that they have an additional receptor for cytophilic antibody which will bind sheep red blood cells coated with IgG (EA 7s) (7,8). B lymphocytes do not react with EA 7s cells but do react with EAC cells (37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter receptor is recognized by the formation of rosettes with sheep red blood cells coated with antibody and complement (EAC). Monocytes, histiocytes, and macrophages also have C3 receptors (7) but differ from B lymphocytes in that they have an additional receptor for cytophilic antibody which will bind sheep red blood cells coated with IgG (EA 7s) (7,8). B lymphocytes do not react with EA 7s cells but do react with EAC cells (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in the field of cellular immunology have now permitted differentiations of different types of mononuclear cells (1)(2)(3)(4)(5)(6)(7). Human lymphocytes may be classified, based upon animal experiments and studies in patients with immunodeficiency states, into at least two groupsthymic-dependent lymphocytes (T cells) and thymicindependent or bone marrow-derived lymphocytes (B cells) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). T cells are thought to mediate reactions of cellular immunity, whereas B cells are primarily concerned with humoral immunity (14,15).…”
Section: Immunologic Characterization Of the Mononuclear Cell Infiltrmentioning
confidence: 99%
“…It is thus significant that the Gm'0 allotype is restricted to the IgG3 sub-class (Martensson and Kunkel, 1965) whilst the Gm' and Gm2 allotypes are restricted to IgGl (Terry, Fahey and Steinberg, 1965; for review see Grubb, 1970). Other workers have shown that whilst IgGI and IgG3 are efficient in-hibitors, both of the phagocytosis of antibody-coated erythrocytes by monocytes (Huber and Fudenberg, 1968) and HEA rosetting by lymphocytes, (Fr0land et al, 1974a), IgGl is much less efficient than IgG3 in attaching to leucocyte Fc receptors (Abramson et al, 1970b).…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of cells in the peripheral blood of acute myeloid leukaemic patients is far larger than in normal peripheral blood, and changes in the percentage of HEA-RFC in AML (Dickler and Kunkel, 1972) Abramson et al (1970b), who showed in addition that Fc fragments and y-1 and y-3 H-chains inhibited rosetting by leucocytes, whilst y-4 H-chain was less inhibitory, and Fab, F(ab')2 and albumin were almost non-inhibitory. Other authors (Messner andJelinek, 1970, Fr0land et al, 1974a) have observed similar inhibition of HEA-RFC, but Dickler and Kunkel (1972) (Dickler and Sachs, 1974).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation